(3ZGjI GdShd Ydi PQjYI GdhUhd aj Yde GdCUhds - (3eMeO Hf eMeO Hf MSf GdGgOds ((3eMeO Hf YHO GdLdjd GdZRi s)
(3ChdgG (B:s
(3fMeOc Gddge Ydi eG efMJfG ef BdGFc HPQjYI GdhUhd , hChdjJfG ef fYeGFc HLeY GdLhGeY hefJgi GdShd s
(3BNQgG (B:s
(3fLhe GdXde ajg JTHjg HdjZ Ydi ePgH GdLeghQ , Ch ESJYGQI JUQjMjI CUdjI Ydi ePgH GdSYO gPG eG jSQg Gddg Gdbhi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda SfI (B1380(3g`s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHg GdTjN eMeO YHO GdLdjd GdZRi GdNGUg HRHjO s
Keywords: (3Gdabg GdESdGejs